Effect of halide anions on structure of 1-butanol monolayer/water interface probed by sum-frequency vibrational spectroscopy - Hue, Nguyen Thi; Tam, Vu Thi Thanh; Tuan, Nguyen Anh (VNU Journal of Science: Mathematics - Physics, 2017)
In this report, we use a sum-frequency generation vibrational spectroscopy to measure SFG spectra from 1-Butanol monolayers on pure water and halide saline solution interfaces. These spectra indicate that halide anions have different effects on the structure of 1-Butanol monolayer/water interfaces. The obtained SFG spectra suggest that the I¯ anions mostly disturb the interfacial structure due to their largest surface propensity among those investigated.